ASSESMENT OF VITAMIN AND TRACE ELEMENTS ENRICHED DIET ON SPERM PARAMETERS IN THE GRASSCUTTER (THRYONOMYS SWINDERIANUS)) IN CAPTIVITY IN IVORY COAST - Abou Joel Landry, OKON; Zhou Patricia, DEH; Etienne Bazago, GOULAI BI; Brahima, Doukoure (International Journal of Research -GRANTHAALAYAH, 2025)
The aim of this work is to improve the reproductive performance of grasscutters in captivity. Thirty (30) grasscutters (Thryonomys swinderianus) aged seven (7) months were selected. They were divided into (two) 2 batches (batch 1 and batch 2) of fifteen individuals in order to receive distinctly (two) 2 types of food. Batch 1 and batch 2 received forage and pellets respectively for one month. The feeding was carried out at the grasscutter farm of Toumodi in the district of Lake. Semen has been collected by using the flotation method. Spermogram and spermocytogram tests were then carried out to make a quantitative and qualitative assessment. Sperm analysis showed that grasscutters fed within the pellet had a higher average sperm concentration and a lower percentage of sperm abnormalities than those fed within the forage. The pH, vitality and mobility percentages were not significant in either batch. It should be noted that pellet-fed grasscutter had better body weight gain, testicular weight gain and semen quality.